2007
DOI: 10.1101/gr.6831208
|View full text |Cite
|
Sign up to set email alerts
|

A code for transcription initiation in mammalian genomes

Abstract: Genome-wide detection of transcription start sites (TSSs) has revealed that RNA Polymerase II transcription initiates at millions of positions in mammalian genomes. Most core promoters do not have a single TSS, but an array of closely located TSSs with different rates of initiation. As a rule, genes have more than one such core promoter; however, defining the boundaries between core promoters is not trivial. These discoveries prompt a re-evaluation of our models for transcription initiation. We describe a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
264
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(288 citation statements)
references
References 59 publications
20
264
0
4
Order By: Relevance
“…This result indicates that TSS distributions are innate aspects of promoters, rather than dynamically controlled transcriptional modes. This is consistent with the finding of Frith et al (2008) that TSS distributions in mammalian promoters, as determined by CAGE, can be predicted from the local DNA sequence. Thus, it may be that the TSS distribution of a promoter can be entirely characterized by assaying at a single biological sample in which the promoter is active.…”
Section: Discussionsupporting
confidence: 92%
“…This result indicates that TSS distributions are innate aspects of promoters, rather than dynamically controlled transcriptional modes. This is consistent with the finding of Frith et al (2008) that TSS distributions in mammalian promoters, as determined by CAGE, can be predicted from the local DNA sequence. Thus, it may be that the TSS distribution of a promoter can be entirely characterized by assaying at a single biological sample in which the promoter is active.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, those with adjacent dominant start sites display a GGG consensus sequence and weak TATA conservation, and those with TSS sites separated by a single nucleotide also exhibit a relatively strong GGG preference and strong TATA use (49). Importantly, TSS use varied among cell types and between normal and tumoral cell lines, indicating that factors other than sequence are important for TSS selection (49,50). Thus it is conceivable that HIV-1 TSS use may be affected by intracellular conditions or change temporally during replication, enabling early production of the longer Cap 2G/ Cap 3G mRNAs used for viral protein synthesis followed by an increase in the production of Cap 1G gRNA transcripts relegated for packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous computational studies of promoter regions upstream of similar TSS initiation patterns in animals have shown that it is possible to predict the locations of NP TSSs from DNA sequence (Frith et al, 2008;Megraw et al, 2009;Rach et al, 2011). A machine learning model called S-Peaker (Megraw et al, 2009) was constructed to use sequence content along with the position specificity and binding affinity of TFBSs to reveal which factors are important for achieving a sharp spatial peak of transcription.…”
Section: Distinct Patterns Of Transcription Initiation Exist In Plantsmentioning
confidence: 99%